Pengaruh Brand Image, Brand Engagement, Brand Love Terhadap Customer Loyalty - PutriHandayani, Wahyu Prabawati Putri Handayani; Dyah Kurniawati; Didik Joko Pitoyo; Wahyu Prabawati Putri Handayani (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
The rise of coffee shops in Madiun City can be seen as both an opportunity and a challenge for coffee businesses. To win the competition, coffee shop entrepreneurs must have a good marketing strategy, including building brand loyalty. A pleasant experience will bring customers back, while an unpleasant experience will cause them to leave. Maintaining brand image, brand engagement, and brand love is crucial for customer loyalty. The study's population consists of coffee shop customers in Madiun. Purposive sampling was used for the study, while multiple regression was used for analysis. The research results show that brand image, brand engagement, and brand love have a significant positive impact on customer loyalty, and brand engagement significantly affects brand love positively. Brand love acts as a partial mediation between brand engagement and customer loyalty. This can be interpreted as brand engagement can have a direct effect on customer loyalty, and brand engagement can have an indirect effect on customer loyalty through brand love.